Ornamentation in Baroque Music: How Is It Appropriately Utilized in Scores and Performances? - Qinqian Fei (Studies in Social Science & Humanities, 2023)
This paper demonstrates the diversity and significance of the flexible use of ornamentation in the Baroque music by analyzing the use of ornamentation in George Frederick Handel’s and Johann Sebastian Bach’s scores, as well as in the instrumental and vocal performance of their musical works. The methodology used in this study was based on a qualitative approach: documentary analysis, using the relevant literature searched to analyse the information and draw conclusions. Details about the following information were obtained by the author: the findings showed that, firstly, ornamentation should be added in a pattern that is within the framework originally framed by the composer and not overly embellished; secondly, the proper incorporation of specific instruments (e.g., harpsichord) and ornamentation makes the piece more baroque; and last but not least, ornamentation should be complementary to the melody and the composition in order to achieve the best effect of it. In general, ornamentation enhances the beauty and enriches the tune of a piece, whose value in Baroque music is unshakable.